THE EFFECT OF SERVICE QUALITY AND TRUST ON CUSTOMER SATISFACTION AT BCA KCP JAKARTA 26 - Sri Windiarti; Suwandi Suwandi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to determine the effect of service quality on customer satisfaction, the effect of customer trust on customer satisfaction, the effect of service quality and customer trust simultaneously on customer satisfaction at BCA KCP Jakarta 26. This study was conducted from October 2020 to February 2021, with the type explanatory research which is also correlational, with a survey method using a questionnaire where the respondents are BCA KCP Jayakarta 26 customers. The population of this study is 216 customers, then through the Slovin formula a sample of 140 respondents is determined, of which 91 are male and 49 female, aged respondents ranged from 17 to 60 years, ranged from 5 to 21 years as a customer. Data analysis was carried out descriptively and hypothesis testing, where the results of the research were descriptivevariables of service quality, customer trust and customer satisfaction are in the categoryclose to agree, meaning that BCA KCP Jayakarta 26 customers agree that BCA KCP Jayakarta 26 meets the indicators for each variable.In the Hypothesis Testing through the SPSS results on the Anova table where the hypothesis (1) Mquality of service affects customer satisfaction. Hypothesis (2) Customer trust has an effect on customer satisfaction. Then on the hypothesis (3) Service quality and customer trust simultaneously affect customer satisfaction.